Systems and strategies for a low cost sense and avoid implementation in small unmanned aircraft - Fonseca, Miguel (2022)
Supervisors: Dr. Rodrigo Martins de Matos Ventura, Major ENGEL João Manuel Moreira Simões Examination Committee: Chairperson: MGEN ENGEL Luís Filipe Basto Damásio; Supervisor: Dr. Rodrigo Martins de Matos Ventura, Major ENGEL João Manuel Moreira Simões; Member of the Committee: TCOR ENGEL Maria de Fátima Alves Nunes